Autoimmune Effects of Lung Cancer Immunotherapy Revealed by Data‐Driven Analysis on a Nationwide Cohort. Issue 2 (11th October 2019) - Yang, Shihao; Yu, Kun‐Hsing; Palmer, Nathan; Fox, Kathe; Kou, S. C.; Kohane, Isaac S.
Abstract : The autoimmune adverse effects of lung cancer immunotherapy are not fully understood at the population level. Using observational data from commercial health insurance claims, we compared autoimmune diseases risk of immune checkpoint inhibitors (including pembrolizumab and nivolumab) and that of chemotherapy using the matching method. By 6 months after treatment initialization, the cumulative incidence of new autoimmune diseases among patients receiving immunotherapy was 13.13% (95% confidence interval (CI), 10.79–15.50%) and that of the matched chemotherapy patients was 6.65% (95% CI, 5.79–7.50%), constituting a hazard ratio (HR) of 1.97 (95% CI, 1.58–2.48). Both pembrolizumab (HR = 2.06 (95% CI, 1.20–3.65), P = 0.0032) and nivolumab (HR = 1.76 (95% CI, 1.39–2.24), P < 0.0001) were associated with higher risks of developing autoimmune diseases, especially for hypothyroidism ( P < 0.0001). Our findings suggest the need to monitor autoimmune side effects of immunotherapy.